The Influences of the Puritan’s Teaching on Young Goodman in Hawthorne’s Young Goodman Brown - Theresia Juwita Purnama; Eddy Pursubaryanto (Lexicon, 2018)
This research attempts to investigate the Puritan’s teachings in Hawthorne’s Young Goodman Brown and the influences of the teachings toward Young Goodman Brown. Formalism was used in this research to analyze the novel. The results of the research show that the Puritan’s teaching of total depravity taught by John Calvin appears in most of the scenes involving Goodman Brown, both explicitly and implicitly. The Puritan’s teaching of total depravity influences Goodman Brown’s thought of people around him. His way of thinking about people around him changed after he returned from the forest. The Puritan’s teaching of total depravity also changes Goodman Brown’s personality indirectly. So, according to the influences of the teachings towards Goodman Brown, they are accepted by Goodman Brown as an invitation to doubt himself and others, to be suspicious of other people’s activities, which eventually leads to an unhappy ending.